Agricultural landscape composition alters ant communities in maize fields more than plant diversity enrichment - DESI NATALIA PASARIBU; AKHMAD RIZALI; HAGUS TARNO; WINDRA PRIAWANDIPUTRA; MIDZON JOHANNIS; DAMAYANTI BUCHORI (Society for Indonesian Biodiversity, 2024)
Abstract. Pasaribu DN, Rizali A, Tarno H, Priawandiputra W, Johannis M, Buchori D. 2024. Agricultural landscape composition alters ant communities in maize fields more than plant diversity enrichment. Biodiversitas 25: 205-213. Fragmented natural habitats in human-modified landscapes play a crucial role in conserving biodiversity. Ants, as keystone species, are integral to terrestrial ecosystems, making it essential to comprehend the factors influencing their survival. This study investigates the impact of agricultural landscape composition and plant diversity enrichment (flowering plants) management on shaping ant communities in maize (Zea mays L.) fields. The research occurred in maize fields surrounded by other crops, semi-natural habitats, and housing areas in Malang District, East Java, Indonesia. The four agricultural areas were divided into control and treatment plots, considering landscape composition parameters, particularly Class Area (CA) and the Number of Patches (NP), measured within a 500 m radius. The landscape around the maize fields was characterized by manually digitizing land use. Six types of plant diversity enrichment were employed in this study: wild cosmos (Cosmos caudatus), white buttercup (Turnera subulata), sunflower (Helianthus annuus), long bean (Vigna unguiculata), ornamental bean (Arachis pintoi), and coral vine (Antigonon leptopus). The study was divided into the dry season (April-July 2022) and the wet season (September-December 2022). Ant sampling was conducted using pitfall traps and, based on generalized linear models, revealed that plant diversity enrichment management did not affect species richness, abundance, or composition of ants. Landscape composition positively influenced ant species richness but negatively impacted species composition, particularly the number of semi-natural habitat patches. Maize crop age also positively influenced ant species richness but negatively affected beta diversity. Wet season was also found to have a negative effect on beta diversity. In conclusion, the proportion of semi-natural habitats in agricultural landscapes and crop age contribute significantly to species richness and species composition of ants.